Executive function and intelligence in the resolution of temporary syntactic ambiguity: an individual differences investigation - Engelhardt, Paul E. (Q J Exp Psychol (Hove), 2016)
In the current study, we examined the role of intelligence and executive functions in the resolution of temporary syntactic ambiguity using an individual differences approach. Data were collected from 174 adolescents and adults who completed a battery of cognitive tests as well as a sentence comprehension task. The critical items for the comprehension task consisted of object/subject garden paths (e.g., While Anna dressed the baby that was small and cute played in the crib), and participants answered a comprehension question (e.g., Did Anna dress the baby?) following each one. Previous studies have shown that garden-path misinterpretations tend to persist into final interpretations. Results showed that both intelligence and processing speed interacted with ambiguity. Individuals with higher intelligence and faster processing were more likely to answer the comprehension questions correctly and, specifically, following ambiguous as opposed to unambiguous sentences. Inhibition produced a marginal effect, but the variance in inhibition was largely shared with intelligence. Conclusions focus on the role of individual differences in cognitive ability and their impact on syntactic ambiguity resolution.